1932
DOI: 10.1152/ajplegacy.1932.101.2.391
|View full text |Cite
|
Sign up to set email alerts
|

The Passage of Urea Between the Blood and the Lumen of the Small Intestine

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1952
1952
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…By the same method, the reflection coefficients and the pore radii were found to be 0.45 and 8 A respectively in the human jejunum and 0.8 and 5.0 A respectively in the human ileum (6). The low reflection coefficient in the jejunum reflects the observation that urea'equilibrates freely between blood and jejunal contents (33)(34)(35). The maximal reflection coefficient in the colon, on the other hand, has to be interpreted as evidence that urea does not penetrate through the colonic mucosa.…”
Section: Colonic Perfusions With Hypertonic Solutionsmentioning
confidence: 92%
“…By the same method, the reflection coefficients and the pore radii were found to be 0.45 and 8 A respectively in the human jejunum and 0.8 and 5.0 A respectively in the human ileum (6). The low reflection coefficient in the jejunum reflects the observation that urea'equilibrates freely between blood and jejunal contents (33)(34)(35). The maximal reflection coefficient in the colon, on the other hand, has to be interpreted as evidence that urea does not penetrate through the colonic mucosa.…”
Section: Colonic Perfusions With Hypertonic Solutionsmentioning
confidence: 92%
“…I n patients with uremia, the concentration of nonprotein nitrogen was higher in the liquid feces. Pendleton and West (1932) presented experimental evidence to show that intestinal mucosa acted to- ward urea as a semipermeable membrane. The data reported here show that-in addition t o serum-peritoneal, biliary, and intestinal fluid can also be used for the diagnosis of renal failure.…”
Section: Resultsiand Discussionmentioning
confidence: 99%
“…As early as 1932, Pendelton and West [118] showed that urea could migrate from plasma to the intestinal lumen. This led to the interest of using various techniques to remove the intestinal urea.…”
Section: Sorbentsmentioning
confidence: 99%